PEDAGOGY AND QUALITY ASSURANCE IN THE DEVELOPMENT OF ONLINE LEARNING FOR ONLINE INSTRUCTORS - Cowham, Terry; Duggleby, Julia (Online Learning, 2005)
The last six years have seen an increasing interest in the use of online technologies for delivering training in the UK, as employers recognize that these technologies can offer a more economic and flexible training package that can be tailored to the priorities of a company and its employees. This article explores the development of the Certificate in Online Learning course, a course developed by an academic organization, The Sheffield College, in partnership with the Chartered Institute of Personnel and Development. The article considers the way in which the strengths and experience of the partners have been brought together to build a new and robust course, based on sound pedagogical principles, that addresses the needs of corporate trainers in the development and delivery of online training. In addition, the article examines the role of the Open College Network, the accrediting body for the course, in ensuring its continued development.